Dual stimuli‐responsive polyamines derived from modified N‐vinylpyrrolidones through CuAAC click chemistry. Issue 8 (22nd October 2015) - del Prado, Anselmo; Navarro, Rodrigo; Levkin, Pavel; Gallardo, Alberto; Elvira, Carlos; Reinecke, Helmut
ABSTRACT: The synthesis via copper(I)‐catalyzed azide alkyne cycloaddition (CuAAC) of three new monomer derivatives of N ‐vinyl‐2‐pyrrolidone (VP) carrying cyclic pyrrolidine, piperidine, and piperazine groups and the corresponding copolymers with unmodified VP is shown. The systems bearing pyrrolidine and piperidine displayed both thermo‐ and pH‐response, which has not been reported previously for a polymer with polyvinylpyrrolidone (PVP) backbone. A broad modulation of the LCST with the copolymer composition and pH was observed in a temperature range 0–100 °C. The polymers carrying piperazine exhibited broad buffering regions and no thermosensitivity. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 1098–1108 Abstract : Novel dual stimuli‐responsive polymers with a true polyvinylpyrrolidone backbone have been synthesized for the first time using a conventional radical copolymerization of N ‐vinylpyrrolidone (VP) and three aminated VP‐derivatives obtained through copper(I)‐catalyzed azide alkyne cycloaddition. These polymers exhibit thermo‐sensitivity, which depends on the nature and the amount of the amine in the polymer, as well as the pH of the media.